Hudud Jarimah From A Criminal Law Perspective Islam: Analysis Of Legal Basis Forms Of Criminal Acts and Evidence System - Hisam Ahyani; Zaid Alfauza Marpaung; Syawaliyah Fitri; Intan Nur aini Harahap; Rabbany Al Ghifari (Jurnal Sahabat ISNU SU, 2024)
Hudud crimes are a category of criminal offenses in Islamic criminal law that have special characteristics because the types of prohibited acts and their sanctions have been firmly established based on the Qur'an and Sunnah. The position of hudud in the Islamic legal system indicates its role as a legal instrument aimed at maintaining public order, protecting public interests, and preventing the emergence of various forms of crime. This study aims to examine the concept of hudud crimes, the normative basis for their application, various forms of criminal offenses included in the hudud category, and their relevance in the development of contemporary legal systems. The method used is normative legal research with a library approach, through a review of Islamic legal sources, such as the Qur'an, hadith, fiqh jinayah literature, and various other Islamic legal references. As a means of imposing sanctions, hudud also has a preventive dimension that aims to suppress the potential for crime through a preventative effect and increasing legal awareness in society. Furthermore, the application of hudud punishments requires stringent evidentiary requirements to minimize the possibility of error in sentencing. Therefore, a comprehensive study of hudud requires attention to normative, philosophical, and sociological aspects to ensure its understanding remains proportionate and relevant to the dynamics of modern legal developments. The concept of hudud itself is part of the study of Islamic jurisprudence (fiqh jinayah), which regulates criminal acts and their sanctions in Islamic law.